2013
DOI: 10.1038/srep01284
|View full text |Cite
|
Sign up to set email alerts
|

Potentially-toxic and essential elements profile of AH1N1 patients in Mexico City

Abstract: During spring of 2009, a new influenza virus AH1N1 spread in the world causing acute respiratory illness and death, resulting in the first influenza pandemic since 1968. Blood levels of potentially-toxic and essential elements of 40 pneumonia and confirmed AH1N1 were evaluated against two different groups of controls, both not infected with the pandemic strain. Significant concentrations of potentially-toxic elements (lead, mercury, cadmium, chromium, arsenic) along with deficiency of selenium or increased Zn/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…During the H1N1 influenza pandemic, Moya et al (17) showed that their group of patients with H1N1 pneumonia was more Se deficient than the control group (non-H1N1 but presenting influenza-like illness). In addition, patients with H1N1 pneumonia who had a blood Se level considered to be optimal for normal Glutathione Peroxidase (GPx) activity (18) recovered faster and had a better survival rate than the patients with H1N1 pneumonia but with lower Se levels (17).…”
Section: Influenza Virusmentioning
confidence: 99%
“…During the H1N1 influenza pandemic, Moya et al (17) showed that their group of patients with H1N1 pneumonia was more Se deficient than the control group (non-H1N1 but presenting influenza-like illness). In addition, patients with H1N1 pneumonia who had a blood Se level considered to be optimal for normal Glutathione Peroxidase (GPx) activity (18) recovered faster and had a better survival rate than the patients with H1N1 pneumonia but with lower Se levels (17).…”
Section: Influenza Virusmentioning
confidence: 99%
“…ICP-MS has been used to assess the concentrations of metals in fluids of patients infected by virus. 129–131 For example, Cu, Zn, and Se were determined in the blood serum of patients with tuberculosis (TB). The effect of HIV co-infection was also assessed in the study.…”
Section: State Of the Art In Metallomics: From Sampling To Quantificamentioning
confidence: 99%
“…A previous study showed that blood concentrations of toxic metals including Cd were significantly higher in H1N1 cases with pneumonia versus pneumonia not caused by H1N1, and two H1N1 cases having highest Cd concentrations did not recover from illness (48). Although limited by the small number of cases, the study suggested that Cd could be a risk factor for inflammatory response and enhanced severity of H1N1 virus infection-induced respiratory diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Cd also interacts with trace elements including selenium, zinc and iron (6,66), providing additional strategies for supplement use (48,56).…”
mentioning
confidence: 99%